Non-circular chainring improves aerobic cycling performance in non-cyclists - Hintzy, F.; Horvais, N. (European Journal of Sport Science, 2016)
Non-circular chainrings alter the crank velocity profile over a pedalling cycle. The aim of this study was to investigate the effect of this altered crank velocity profile on the aerobic performance compared to a circular chainring (CC). Ten male non-cyclists performed two incremental maximal tests at 80 rpm on a cycle ergometer: one with a circular (Shimano) and the other with a non-circular chainring Osymetric® (Somovedi), at least 50 h apart. Each test started with a workload of 100 W lasting 3 min. During the first 12 min, the workload was increased by 30 W every 3 min. Thereafter, the workload was increased by 30 W every 2 min until exhaustion. The power output, the intra-cycle crank angular velocity and the physiological parameters were monitored continuously, averaged over the last 30 s of each increment and at exhaustion, and compared for the two chainrings. Results showed a higher maximal aerobic power attained with the non-circular chainring (362.6 ± 37.9 vs. 338.8 ± 32.6 W, p < .001; moderate effect), which could be explained by a significantly lower energy expenditure during the first increment at 100 W. It could be hypothesised that the use of the non-circular chainring allowed saving a small part of energy expenditure throughout the test, allowing the exhaustion of the subject at a higher increment for a similar maximal energy expenditure, in comparison with a CC. Although this improvement is obtained only for non-cyclists, it allowed highlighting the link between cycling equipment modifying the pedalling motion and physiological responses.